Treatment of [99mTc]Tc‐hydroxy‐diphosphonate ([99mTc]Tc‐HDP) extravasation using hyaluronidase - Kevin R. Doornhof; Quido de Lussanet de la Sablonière; Stijn L. W. Koolen; Mark W. Konijnenberg (Wiley, 2024)
Abstract Extravasation of 99mTc‐labeled radiopharmaceuticals is generally considered to require no specific intervention. In the presented case, the use of hyaluronidase could have minimized the adverse effects resulting from such an extravasation. Currently, no guidelines exist regarding the use of hyaluronidase after extravasation of [99mTc]Tc‐HDP. Considering the low risk of administering hyaluronidase, it should be considered to limit the risk of injury after extravasation of [99mTc]Tc‐HDP.